2007
DOI: 10.1158/1535-7163.mct-06-0513
|View full text |Cite
|
Sign up to set email alerts
|

Molecular correlates of gefitinib responsiveness in human bladder cancer cells

Abstract: We characterized the effects of the small molecule epidermal growth factor receptor (EGFR) inhibitor gefiti-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
36
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 36 publications
9
36
0
1
Order By: Relevance
“…Loss of other epithelial markers and gain of the mesenchymal marker vimentin showed a similar but looser association. We previously showed a similar relationship with gefitinb (17), but here, we were able to establish a causal association by silencing E-cadherin expression in two sensitive urothelial carcinoma cells and thereby imparting resistance to cetuximab.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Loss of other epithelial markers and gain of the mesenchymal marker vimentin showed a similar but looser association. We previously showed a similar relationship with gefitinb (17), but here, we were able to establish a causal association by silencing E-cadherin expression in two sensitive urothelial carcinoma cells and thereby imparting resistance to cetuximab.…”
Section: Discussionsupporting
confidence: 65%
“…A recent gene profiling study showed that resistance to erlotinib correlated closely with epithelial-to-mesenchymal transition in non -small cell lung cancer cell lines and patient tumors (16). We have recently reported similar findings with gefitinib in a series of urothelial carcinoma cell lines that we have expanded upon in this report (17).…”
supporting
confidence: 76%
“…Two recent reports have suggested that epithelial-tomesenchymal transition (EMT) predicts in vitro sensitivity and clinical activity of erlotinib in NSCLC (17,18) whereas another report has shown a correlation between EMT and erlotinib sensitivity in pancreatic and colorectal tumor cell lines (19). Similar results have been reported for gefitinib sensitivity in cell lines from NSCLC (20), head and neck squamous cell carcinoma (20), and bladder cancer (21). Consistent with these studies, restoration of E-cadherin expression increases sensitivity to gefitinib in NSCLC (22).…”
Section: Introductionmentioning
confidence: 53%
“…An EMT-like transition has been associated with NSCLC tumor cell, xenograft and patient insensitivity to selective EGFR tyrosine kinase inhibition [11][12][13], in part from EGFR independent activation of either or both the PI3 0 kinase or Mek-Erk pathways [14]. Similar data correlating EMT status to sensitivity to EGFR TKIs have been reported in pancreatic, CRC [14] bladder [15] and HNSCC [16] cell lines, xenografts and in patients samples [13]. The molecular determinants to alternative routes of activation of the PI3 0 kinase and/or Erk pathways, which can bypass cellular sensitivity to EGF receptor inhibitors, have been actively investigated.…”
Section: Introductionmentioning
confidence: 56%